Satisfactory Functional Outcome and Significant Correlation with the Length of Haglund’s Deformity after Endoscopic Calcaneoplasty: A Minimum 4-Year Follow-Up Study - Hossam Fathi Mahmoud; Walid Feisal; Fahmy Samir Fahmy (Advances in Orthopedics)
Background. Haglund’s syndrome is a posterosuperior calcaneal prominence with posterior heel pain causing functional disability to the patient. Operative treatment is indicated after failure of conservative measures and includes resection of the bony hump along with retrocalcaneal bursectomy. This study aimed to evaluate the functional outcome and degree of patient satisfaction after endoscopic resection of Haglund’s deformity with assessment of correlation with the length of bony exostosis. Methods. Seventeen patients (21 feet) with a mean age of 44.7 ± 5.1 years were included in this study. Six females and 11 males underwent endoscopic calcaneoplasty. Clinical outcome evaluation included the assessment of the visual analog scale (VAS) and the American Orthopedic Foot and Ankle Society score (AOFAS). The preoperative and postoperative lengths of bony exostosis were measured radiologically. The paired t test and the Wilcoxon signed-rank test compared the preoperative and final postoperative means. P<0.05 was considered statistically significant. Results. The mean follow-up period was 56.4 ± 5.1 months. Statistically significant improvements in the preoperative mean of AOFAS (from 55.7 ± 9.3 to 94.3 ± 7.1) and VAS (from 8.1 ± 1.4 to 0.7 ± 1.04) at the final follow-up were noted P<0.0001. There was a statistically significant correlation between clinical scores (AOFAS and VAS) and the final postoperative length of the bone above parallel pitch lines (PPLs). The patients were satisfied and returned to their previous activities without reporting major morbidities except one patient who had mild pain with exertion. Conclusion. Endoscopic calcaneoplasty is a safe, less invasive surgical procedure for the management of Haglund’s syndrome after failure of conservative treatment. It provided a satisfactory clinical result without serious complications at a minimum 4-year follow-up.